Odpowiedź :
Odpowiedź:
a) [tex]\frac{1}{2} +\frac{1}{3} +\frac{1}{4} =\frac{6}{12} +\frac{4}{12} +\frac{3}{12} =\frac{13}{12} =1\frac{1}{12}[/tex]
b) [tex]1\frac{2}{5} +3\frac{4}{10} +2\frac{1}{2} =\frac{7}{5} +\frac{34}{10} +\frac{5}{2} =\frac{14}{10} +\frac{34}{10}+\frac{25}{10} =\frac{73}{10} =7\frac{3}{10}[/tex]
c) [tex]4\frac{1}{3} -2\frac{2}{5} +1\frac{1}{5} =\frac{13}{3} -\frac{12}{5} +\frac{6}{5} =\frac{65}{15} -\frac{36}{15} +\frac{18}{15} =\frac{47}{15} =3\frac{2}{15}[/tex]
d) [tex]7-3\frac{1}{3} -2\frac{1}{8} =\frac{7}{1} -\frac{10}{3} -\frac{17}{8} =\frac{168}{24} -\frac{8}{24}-\frac{51}{24} =\frac{109}{24} =4\frac{9}{24} =4\frac{3}{8}[/tex]
e) [tex]3\frac{3}{4}-2\frac{2}{3} +6-3\frac{5}{6} =\frac{15}{4} -\frac{8}{3} +\frac{6}{1} -\frac{23}{6} =\frac{45}{12} -\frac{32}{12} +\frac{72}{12} -\frac{46}{12} =\frac{39}{12} =\frac{13}{4}=3\frac{1}{4}[/tex]
f) [tex]10-(2\frac{1}{9} -\frac{1}{2} +1\frac{5}{6} )=10(\frac{19}{9} -\frac{1}{2} +\frac{11}{6} )=10-(\frac{38}{19} -\frac{9}{18} +\frac{33}{18} )=10-\frac{62}{18}=\frac{10}{1} -\frac{31}{9} =\frac{90}{9} -\frac{31}{9} =\frac{59}{9} =6\frac{5}{9}[/tex]
g) [tex](4\frac{1}{3}-2\frac{2}{5} )-(6\frac{3}{5} -5\frac{2}{3})=(\frac{13}{3}-\frac{12}{5})-(\frac{33}{5} -\frac{17}{3} )=(\frac{65}{15} -\frac{38}{15} )-(\frac{99}{15} -\frac{85}{15} )=\frac{27}{15} -\frac{14}{15} =\frac{13}{15}[/tex]
h) [tex]3\frac{1}{4} +2\frac{2}{5} -(4\frac{1}{3} -2\frac{2}{3} )=\frac{13}{4}+\frac{12}{5} -(\frac{13}{3}-\frac{8}{3})= \frac{13}{4}+\frac{12}{5} -\frac{5}{3} =\frac{195}{60} +\frac{144}{60} -\frac{100}{60} =\frac{239}{60} =3\frac{59}{60}[/tex]